The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s10461-021-03177-0
|View full text |Cite
|
Sign up to set email alerts
|

Black and Latino Persons Living with HIV Evidence Risk and Resilience in the Context of COVID-19: A Mixed-Methods Study of the Early Phase of the Pandemic

Abstract: The COVID-19 pandemic has great potential to disrupt the lives of persons living with HIV (PLWH). The present convergent parallel design mixed-methods study explored the early effects of COVID-19 on African American/Black or Latino (AABL) long-term survivors of HIV in a pandemic epicenter, New York City. A total of 96 AABL PLWH were recruited from a larger study of PLWH with non-suppressed HIV viral load. They engaged in structured assessments focused on knowledge, testing, trust in information sources, and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
66
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(98 citation statements)
references
References 42 publications
(41 reference statements)
15
66
4
Order By: Relevance
“…COVID-19 containment measures taken in Ethiopia had a signi cant contribution in halting the spread of COVID-19 in Ethiopia; however, they had their own implications on HIV care and treatment services as the response from the HIV patients indicated. Transport disruption, partial lockdown that impaired mobility, and income reduction were signi cant factors for missing health care visits, which was in agreement with previous studies conducted in Ethiopia [10, 42, ] and elsewhere in the world [43][44][45][46][47][48][49][50] that COVID-19 containment measure had a signi cant impact on patients' access to healthcare facilities.…”
Section: Discussionsupporting
confidence: 88%
“…COVID-19 containment measures taken in Ethiopia had a signi cant contribution in halting the spread of COVID-19 in Ethiopia; however, they had their own implications on HIV care and treatment services as the response from the HIV patients indicated. Transport disruption, partial lockdown that impaired mobility, and income reduction were signi cant factors for missing health care visits, which was in agreement with previous studies conducted in Ethiopia [10, 42, ] and elsewhere in the world [43][44][45][46][47][48][49][50] that COVID-19 containment measure had a signi cant impact on patients' access to healthcare facilities.…”
Section: Discussionsupporting
confidence: 88%
“…Studies also investigated factors that may have contributed to increased COVID-19 distress. For example, because of heightened concerns for contracting COVID-19 among PLWH, conflicting public health messaging and misinformation may have fueled COVID-19 stress [48]. One barrier to COVID-19 information messaging was a lack of trust in public health information sources, such as the CDC and health departments.…”
Section: Emotional Distressmentioning
confidence: 99%
“…One barrier to COVID-19 information messaging was a lack of trust in public health information sources, such as the CDC and health departments. Using the same measures, two independent studies showed that PLWH in New York City [48] and Atlanta, GA [49], demonstrated low levels of trust in COVID-19 information from all public health institutions, with greater trust in local and state health departments than trust in the CDC and other federal agencies. It is important to note that like social isolation, not all studies provide evidence for adverse effects of COVID-19 on emotional distress among PLWH.…”
Section: Emotional Distressmentioning
confidence: 99%
See 2 more Smart Citations